Influence of Temperature and pH on Spectral Characteristics of Horseradish Peroxidase in Aqueous Buffer as well as in Nonionic Reverse Micellar System - Kumar, Anil (Asian Journal of Chemistry, 2015)
In this article, temperature dependent spectral characteristics of peroxidase dissolved in aqueous buffer as well as in nonionic reverse micellar systems are reported at different pH values over a wide range of temperature. It is found that the soret band of peroxidase remains unchanged in reverse micellar media as compared to aqueous buffer solution at lower temperature (T £ 20 °C) and then gradually changes as the temperature is increased. At 35 °C the total shape of the spectra changes and at 50 °C it is much more in a distorted form. As the temperature is gradually increased, the total shape of the soret band changes into somewhat random type. This change of the spectral behaviour of horseradish peroxidase at different temperature can be attributed to the structural changes of the enzyme molecule encapsulated inside the aqueous core of the reverse micelles. The absorption spectra of peroxidase with temperature have been studied in reverse micellar media at various Wo. Two types of behaviour of the enzymes are found inside the micellar aqueous core; (i) in the temperature range of 10-30 °C and (ii) in the temperature range 30-50 °C. Again for Wo £ 15 the enzyme behaves in the similar fashion and W > 15 and in the aqueous system, the enzyme behaves in a different fashion. The absorption values slowly increases for Wo £ 15 and attains constant value after that. For Wo = 18 and 20, the absorption value remains constant till the temperature is 30 °C and above that it slowly decreases. The change in absorption spectra of peroxidase molecule with temperature is due to some structural perturbation of the enzyme molecule in reverse micellar media.